Effectiveness of Honey Soy Milk on Hemoglobin Improvement among Adolescent Girls with Menstrual Anemia: A Quasi-Experimental Study - Yuniza, Yuniza; Ginanjar, Marwan Riki; Ulaa, Mar’atun; Williams, Brett (Journal of Applied Nursing and Health, 2026)
Background: Anemia is a common health problem among adolescent girls, primarily due to iron deficiency and blood loss during menstruation. Honey contains bioactive compounds beneficial to health, including the improvement of metabolism and hematological status. This study aims to determine the effect of honey soy milk on hemoglobin (Hb) levels among adolescent girls with menstrual anemia. Methods: This quantitative study employed a quasi-experimental design with one group pretest–posttest, conducted at an educational institution in Indonesia. A total of 25 adolescent girls with menstrual anemia were selected using purposive sampling based on inclusion and exclusion criteria. The intervention consisted of administering 200 mL of honey soy milk twice daily for 5 consecutive days during menstruation. Hemoglobin levels were measured in g/dL using an EasyTouch GCHb digital analyzer before and after the intervention. Data analysis followed the Transparent Reporting of Evaluations with Nonrandomized Designs (TREND) guidelines. Results: The mean hemoglobin level before the intervention was 11.15 ± 1.72 g/dL, and after the intervention, it increased to 12.92 ± 1.87 g/dL. Statistical testing showed a significant difference (p < 0.001), indicating that honey soy milk effectively improved Hb levels among participants. Conclusion: Honey soy milk is effective in increasing hemoglobin levels in adolescent girls with menstrual anemia. These findings support the use of functional foods as an adjunctive strategy in anemia prevention and management programs for adolescents